2014
DOI: 10.1093/jrr/rru086
|View full text |Cite
|
Sign up to set email alerts
|

Whole-pelvic volumetric-modulated arc therapy for high-risk prostate cancer: treatment planning and acute toxicity

Abstract: The objectives of this study were to evaluate dosimetric quality and acute toxicity of volumetric-modulated arc therapy (VMAT) and daily image guidance in high-risk prostate cancer patients. A total of 100 consecutive high-risk prostate cancer patients treated with definitive VMAT with prophylactic whole-pelvic radiotherapy (WPRT) were enrolled. All patients were treated with a double-arc VMAT plan delivering 52 Gy to the prostate planning target volume (PTV), while simultaneously delivering 46.8 Gy to the pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…In the current study, there was no correlation between the acute toxicity and the dosimetric parameters. The same finding was also observed by other investigators [29] [32] and [33]. This lack of correlation between toxicity and dosimetric variables could be due to the low dosimetric parameters and low frequencies of the severe acute toxicities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, there was no correlation between the acute toxicity and the dosimetric parameters. The same finding was also observed by other investigators [29] [32] and [33]. This lack of correlation between toxicity and dosimetric variables could be due to the low dosimetric parameters and low frequencies of the severe acute toxicities.…”
Section: Discussionsupporting
confidence: 88%
“…Also, Deville et al, [28] reported 50% grade II toxicity for both GI and GT. On the other hand, Ishii et al, [29] [31]. Therefore, the acceptably low incidence of acute toxicity in the current study might contribute to decreasing the late side effects in further follow-up.…”
Section: Discussionmentioning
confidence: 51%
“…Although several recent studies have reported early clinical results of VMAT for prostate cancer, [12][13][14] to the best of our knowledge, there are no published clinical studies comparing WP VMAT with PO VMAT. Therefore, there is a need to demonstrate whether the use of WPRT could result in increased toxicity when VMAT is performed.…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic lymph nodes, prostate, and seminal vesicles were treated by 5 authors 62 , 64 , 66 68 using a single- to triple-arc technique, with doses ranging from 46.8 Gy for nodal coverage to 78 Gy for prostate irradiation. Almost all used IG as kV or CBCT, and ~335 patients were treated from 2012 to 2016.…”
Section: Resultsmentioning
confidence: 99%